2019
DOI: 10.1029/2019gl082352
|View full text |Cite
|
Sign up to set email alerts
|

Short‐ and Long‐Term Variations in the Reykjanes Geothermal Reservoir From Seismic Noise Interferometry

Abstract: The Reykjanes Geothermal System (RGS) is a high‐temperature geothermal system located on the Reykjanes peninsula, a transtensional plate‐boundary zone located on the southwestern tip of Iceland. The area is characterized by high seismicity, recent volcanism, and high‐temperature geothermal fields. We use seismic noise records from April 2014 to August 2015 to study stress changes and potential deformation of the subsurface caused by injection and production operations at RGS through seismic interferometry. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 58 publications
2
20
0
Order By: Relevance
“…Cross-correlations of ambient seismic noise form the basis of many applications in seismology from site effects studies (e.g., Aki, 1957;Roten et al, 2006;Bard et al, 2010;Denolle et al, 2013;Bowden et al, 2015) to ambient noise tomography (e.g., Shapiro et al, 2005;Yang et al, 2007;Nishida et al, 2009;Haned et al, 2016;de Ridder et al, 2014;Fang et al, 2015;Singer et al, 2017) and coda wave interferometry (e.g., Sens-Schönfelder and Wegler, 2006;Brenguier et al, 2008;Obermann et al, 2013;Sánchez-Pastor et al, 2019). Auto-correlations of the ambient noise are also increasingly used to study seismic interfaces as suggested by Claerbout (1968) (e.g., Taylor et al, 2016;Saygin et al, 2017;Romero and Schimmel, 2018) and to monitor subsurface properties (Viens et al, 2018;Clements and Denolle, 2018).…”
Section: Motivationmentioning
confidence: 99%
“…Cross-correlations of ambient seismic noise form the basis of many applications in seismology from site effects studies (e.g., Aki, 1957;Roten et al, 2006;Bard et al, 2010;Denolle et al, 2013;Bowden et al, 2015) to ambient noise tomography (e.g., Shapiro et al, 2005;Yang et al, 2007;Nishida et al, 2009;Haned et al, 2016;de Ridder et al, 2014;Fang et al, 2015;Singer et al, 2017) and coda wave interferometry (e.g., Sens-Schönfelder and Wegler, 2006;Brenguier et al, 2008;Obermann et al, 2013;Sánchez-Pastor et al, 2019). Auto-correlations of the ambient noise are also increasingly used to study seismic interfaces as suggested by Claerbout (1968) (e.g., Taylor et al, 2016;Saygin et al, 2017;Romero and Schimmel, 2018) and to monitor subsurface properties (Viens et al, 2018;Clements and Denolle, 2018).…”
Section: Motivationmentioning
confidence: 99%
“…Interferometric techniques may well play an important role in the future of geothermal exploration (e.g., [8]). In particular, this applies to tomographic travel time inversions: contrary to travel time tomography exploiting earthquake signals, the spatial sampling by the interferometric ray paths does not suffer from either a limited number of earthquakes or an irregular distribution of these earthquakes [3].…”
Section: Introductionmentioning
confidence: 99%
“…Since then, the detection of temporal changes in the codafrom repeating earthquakes or more recently from ambient noise correlations-has been successfully applied in various settings such as: CO 2 and geothermal fluid injection studies (Ugalde et al 2013;Hillers et al 2015;Obermann et al 2015;Taira et al 2018;Sánchez-Pastor et al 2019), volcanoes (e.g. Poupinet et al 1996;Grêt et al 2005;Sens-Schönfelder & Wegler 2006;Brenguier et al 2016;Donaldson et al 2017;Sánchez-Pastor et al 2018), fault zones (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, retrieving the spatial Coda kernels in elastic media 935 distribution of scattering (velocity, respectively) changes from a set of coda-wave decorrelation (phase shift, respectively) measurements amounts to solving an inverse problem. This was successfully applied to: numerical simulations (Planès 2013;Planès et al 2015;Kanu & Snieder 2015b;, locating precursors of volcanic eruptions (Obermann et al 2013a;Lesage et al 2014;Sánchez-Pastor et al 2018), assessing fault zone damages (Froment 2011;Obermann et al 2014), monitoring subsurface changes due to high-pressure fluid injections (Hillers et al 2015;Obermann et al 2015;Sánchez-Pastor et al 2019) and monitoring crack/fissure growth in concrete blocks (Larose et al 2010(Larose et al , 2015Zhang et al 2016).…”
Section: Introductionmentioning
confidence: 99%